2015
DOI: 10.1111/1756-185x.12564
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms are associated with key health outcomes in women with fibromyalgia: a cross-sectional study

Abstract: Depressed women with FM exhibited higher symptom severity and reported worse physical fitness and quality of life than their non-depressed peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…18 Furthermore, psychological symptoms were found to be associated with disease severity, poor physical fitness and deterioration in quality of life (QoL) in the patients with FM. 19 Type D personality is a distressed personality type involving two personality traits, namely negative affectivity and social inhibition, which are described as tendency to experience negative emotions and to inhibit self-expression in social relationships, respectively. 20 Individuals with negative affectivity commonly concentrate on negative aspects of life and are likely to experience negative feelings such as distress, dissatisfaction, irritability, anxiety and depression.…”
mentioning
confidence: 99%
“…18 Furthermore, psychological symptoms were found to be associated with disease severity, poor physical fitness and deterioration in quality of life (QoL) in the patients with FM. 19 Type D personality is a distressed personality type involving two personality traits, namely negative affectivity and social inhibition, which are described as tendency to experience negative emotions and to inhibit self-expression in social relationships, respectively. 20 Individuals with negative affectivity commonly concentrate on negative aspects of life and are likely to experience negative feelings such as distress, dissatisfaction, irritability, anxiety and depression.…”
mentioning
confidence: 99%
“…Of interest, among patients who moved to a worse cluster, the symptoms that drove the change were predominantly depression and anxiety. This is not surprising since previous studies report the detrimental effects of comorbid depression and anxiety on overall symptom severity [ 42 , 43 ] and because of the bidirectional effect of depression in samples of patients with fibromyalgia [ 44 ]. Research has also demonstrated that patients with fibromyalgia with comorbid mood disorders and anxiety tend to have poorer outcomes than patients with predominantly physical and lower psychological symptoms [ 42 ].…”
Section: Discussionmentioning
confidence: 80%
“…This is not surprising since previous studies report the detrimental effects of comorbid depression and anxiety on overall symptom severity [ 42 , 43 ] and because of the bidirectional effect of depression in samples of patients with fibromyalgia [ 44 ]. Research has also demonstrated that patients with fibromyalgia with comorbid mood disorders and anxiety tend to have poorer outcomes than patients with predominantly physical and lower psychological symptoms [ 42 ]. Our finding that mood and anxiety tended to drive changes in cluster categorization highlights the importance of regular mood and anxiety assessment and referral to mental health specialists, as appropriate, in patients with fibromyalgia who have worsening symptoms.…”
Section: Discussionmentioning
confidence: 80%
“…This is not surprising since previous studies report the detrimental effects of comorbid depression and anxiety on overall symptom severity [42,43] and because of the bidirectional effect of depression in samples of patients with fibromyalgia [44]. Research has also demonstrated that patients with fibromyalgia with comorbid mood disorders and anxiety tend to have poorer outcomes than patients with predominantly physical and lower psychological symptoms [42].…”
Section: Discussionmentioning
confidence: 94%